Mortality in asbestos cement workers in Pavia, Italy: A cohort study - Oddone, Enrico; Ferrante, Daniela; Tunesi, Sara; Magnani, Corrado (American journal of industrial medicine, 2017)
Background The aim of this study was to describe the mortality of a cohort of asbestos‐cement workers in the largest plant in the most industrialized Italian region (Lombardy). Methods A cohort study was carried out on 1818 subjects, corresponding to 47 536.1 person‐years of observation. Standardized mortality ratios (SMRs) were computed for the major causes of death. Results Increased SMRs were observed for pleural, peritoneal and lung cancers, and for asbestosis (SMR 26.73, 95% Confidence Interval (CI) 20.99‐33.55; 9.15, 95%CI 5.00‐15.34; 1.48, 95%CI 1.27‐1.72; and 368.05, 95%CI 214.40‐589.29, respectively). No excess in mortality for laryngeal cancer was observed (SMR 0.70, 95%CI 0.30‐1.39). An increased mortality for ovarian cancer (SMR 3.64, 95%CI 0.99‐9.33) was observed, although it was not statistically significant. Among men, mortality for pleural malignant mesothelioma was observed to be related to the duration of exposure, though not to latency. Conclusions The results of this study are generally consistent with present knowledge. Conversely, our results do not support the hypothesis that pleural malignant mesothelioma risk indefinitely increases after exposure, suggesting instead that the alternative hypothesis of a risk plateau or decrease after a time since first exposure of more than 40 years is more consistent with the observed data.